3D biofabrication for soft tissue and cartilage engineering. (August 2020) - Turnbull, Gareth; Clarke, Jon; Picard, Frédéric; Zhang, Weidong; Riches, Philip; Li, Bin; Shu, Wenmiao
Abstract: Soft tissue injuries (STIs) affect patients of all age groups and represent a common worldwide clinical problem, resulting from conditions including trauma, infection, cancer and burns. Within the spectrum of STIs a mixture of tissues can be injured, ranging from skin to underlying nerves, blood vessels, tendons and cartilaginous tissues. However, significant limitations affect current treatment options and clinical demand for soft tissue and cartilage regenerative therapies continues to rise. Improving the regeneration of soft tissues has therefore become a key area of focus within tissue engineering. As an emerging technology, 3D bioprinting can be used to build complex soft tissue constructs "from the bottom up, " by depositing cells, growth factors, extracellular matrices and other biomaterials in a layer-by-layer fashion. In this way, regeneration of cartilage, skin, vasculature, nerves, tendons and other bodily tissues can be performed in a patient specific manner. This review will focus on recent use of 3D bioprinting and other biofabrication strategies in soft tissue repair and regeneration. Biofabrication of a variety of soft tissue types will be reviewed following an overview of available cell sources, bioinks and bioprinting techniques. Graphical abstract: This review will focus on recent use of 3D biofabrication techniques to regenerate cartilage and a range of soft tissue types found in the body. An initial overview of currently available cell sources, bioinks and biofabrication techniques for cartilage and soft tissue regeneration will be provided. Mechanical performance, biocompatibility, bioactivity, method of biofabrication and potential clinical translation of recent tissue engineered soft tissue constructs will then be discussed. Image, graphical abstract